Cariogenicity of infant formulas using desalivated rat models - Dycoco, Abbie V.; Ancheta, Eddieliza B.; Medina III., Vicente O. (Adviser).
Baby bottle tooth decay has been attributed to some infant formulas. This study aims to determine the cariogenic potential of two commercially available infant formulas (Bonamil and Promil2) and to determine which among the two has the higher level of cariogenic potential. This experimental study used 12 desalivated Sprague-dawley rats, randomly divided into four groups namely (-) negative control group, (+) control group, Bonamil group and Promil2 group. The rat models were fed, ad libitum with distilled water, 5% sucrose solution, Bonamil and Promil2 respectively. At the end of 18 experimental days, the mandibles were collected and the teeth were scored using the Modified Keyes method through slide photos taken at 3 times magnification. The result yielded the following scores: (+) control - 12; Bonamil - 11.8; Promil2 - 9.88; (-) control - 6.5. Despite their differences, statistical analysis showed no significant difference in the (+) control, Bonamil and Promil2 groups at 0.05 level of significance. This study concluded that Bonamil and Promil2 are equally potentially cariogenic.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Infant formulas; Cariogenic agents; Dental caries